KESIAPSIAGAAN PEMERINTAH KABUPATEN BREBES DALAM MENGHADAPI BENCANA BANJIR DIMASA PADEMI COVID-19 - AHMAD FATKUL FIKRI; Syamsul Maarif; IDK Kerta Widana; Titisari Haruming Tyas (Jurnal Ilmu Pemerintahan Widya Praja, 2020)
The research entitled "Brebes Regency Government Preparedness in Facing Flood Disaster during the Covid-19 Pandemic". This study aims to analyze the level of preparedness of the Brebes Regency government is facing flood disasters during the Covid-19 pandemic. The method used in this research is descriptive qualitative. In collecting data using interviews, observation, and documentation. Meanwhile, the analysis used the Miles, Huberman, and Saldana model analysis technique. The results of this study indicate that 1). The Brebes Regency Government has good knowledge of the threat of floods and covid-19 disasters; 2). The Brebes Regency Government does not yet have a flood disaster contingency plan in the face of a pandemic; 3). The early warning system for the threat of flooding is still conventional; 4). The Brebes Regency Government has never carried out a flood simulation during the Covid-19 pandemic 5). The Brebes Regency Government has collaborated with the community in flood disaster preparedness. The recommendations from the authors are 1). Formulate regulations for disaster management during a pandemic; 2). Prepare the location of evacuation places that meet health protocols; 3). Formulate a contingency plan for the threat of floods during a pandemic; 4) Train volunteers in handling victims of suspected covid-19; 5). Improve coordination and cooperation in civil-military relations.